Association between parity and markers of inflammation: The multi-ethnic study of atherosclerosis - Ezeigwe, Angelica; Ogunmoroti, Oluseye; Minhas, Anum S.; Rodriguez, Carla P.; Kazzi, Brigitte; Fashanu, Oluwaseun E.; Osibogun, Olatokunbo; Kovell, Lara C.; Harrington, Colleen M.; Michos, Erin D. (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Multiparity has been associated with increased risk of cardiovascular disease (CVD). Inflammation may be a mechanism linking parity to CVD. We investigated the association between parity and later-life markers of inflammation. Methods: We studied 3,454 female MESA participants aged 45-84, free of CVD, who had data on parity and inflammatory markers. Parity was categorized as 0 (reference), 1-2, 3-4, or ≥5. Linear regression was used to evaluate the association between parity and natural log-transformed levels of fibrinogen, D-dimer, GlycA, high sensitivity C-reactive protein (hsCRP), and interleukin-6 (IL-6). Results: Mean age was 62±10 years. The proportion of women with nulliparity, 1-2, 3-4, and ≥5 live births were 18%, 39%, 29% and 14%, respectively. There was no association between parity and fibrinogen. Women with grand multiparity (≥5 live births) had 28%, 10% and 18% higher levels of hsCRP, IL-6 and D-dimer, respectively, compared to nulliparous women, after adjustment for demographic factors. After additional adjustment for CVD risk factors, women with 1-2 and 3-4 live births had higher hsCRP and women with 1-2 live births had higher GlycA. Conclusion: In this diverse cohort of middle-to-older aged women, we found that higher parity was associated with some inflammatory markers; however, these associations were largely attenuated after adjustment for CVD risk factors. There was no clear dose-response relationship between parity and these inflammatory markers. Future studies are needed to evaluate how inflammation may influence the link between parity and CVD and whether healthy lifestyle/pharmacotherapies targeting inflammation can reduce CVD risk among multiparous women.